Ramli Abdul Wahid and His Thoughts on Islamic Education - Irvan Mangunsong; Usiono Usiono (Universitas Muhammadiyah Enrekang, 2024)
Ramli Abdul Wahid and His Thought on Islamic Education. This paper discusses the biography of Ramli Abdul Wahid, a North Sumatra scholar who has multidisciplinary thinking. He is a Hadith expert, but discusses various disciplines and one of them is Islamic education. This research is a qualitative research with a character study approach. From the research conducted, the author concludes that Ramli Abdul Wahid's Islamic education thinking is motivated by his educational history and his position as chairman of the fatwa commission at the Indonesian Ulama Council of North Sumatra (MUI SU) and Al-Jam'iyatul Washliyah Medan. Therefore, the orientation of Islamic education according to him is that it must be in accordance with Islamic values based on the Qur'an and Hadith.